MCR-1 Gene Encoded Colistin-Resistant Escherichia coli in Raw Chicken Meat and Bean Sprouts in Malaysia - Erkihun Aklilu; Kausalya Raman (International Journal of Microbiology)
This study was conducted to detect the presence of colistin-resistant Escherichia coli (E. coli) in raw chicken meat and bean sprouts collected from local markets and to determine the antimicrobial resistance patterns of the E. coli isolates. A total of 100 samples, comprised of 50 raw chicken meat and 50 bean sprouts, were collected and processed. Kirby-Bauer method was used to determine the antimicrobial resistance patterns, and PCR amplification was used to detect E. coli species-specific and colistin resistance (mcr-1 and mcr-2) genes. The results showed that 52.1% (12/23) of the E. coli isolated from raw chicken meat were positive for the colistin resistance encoding gene, mcr-1, whereas all the E. coli isolates from bean sprouts were negative for colistin resistance encoding genes. The findings show that chicken meat contaminated with colistin-resistant E. coli may pose public health risk to the consumers. Hence, prudent usage of antibiotics and hygienic handling of food items helps to prevent and combat the risks of spreading of colistin-resistant E. coli and the public health risks it may pose. More comprehensive and large-scale studies focusing on all the possible sources of colistin-resistant E. coli are recommended.